Gadai dalam Perspektif KUHPerdata dan Hukum Islam - Hanna Masawayh Qatrunnada; Lailatul Choiriyah; Nurul Fitriani (Maliyah : Jurnal Hukum Bisnis Islam, 2018)
This article discusses the law of pawn in terms of the Civil Code and Islamic law. This article is the result of a literature study and is qualitative. Data about pawning is collected through books, journals, and the internet. After the data was collected, it was classified and analyzed descriptively. The results of the discussion concluded that pawning in the Civil Code is regulated in Book II Chapter 20, Article 1150 to Article 1161, while in Islamic law it is included in the discussion of muamalah fiqh. In terms of the Civil Code and Islamic law, they have the same thing that the pawn is collateral for goods because of the existence of accounts payable, and both allow pawning law. The existence of a pawning contract has implications for legal consequences. The Civil Code regulates these provisions in its articles. Islamic law allows pawning based on the arguments of the Koran, Sunnah, and ijma'. Pawn contains benefits, namely to help someone who is experiencing difficulties in their daily activities. The pawn (ar-Rahn) has certain pillars and conditions that must be fulfilled so that the pawn can be implemented based on goodness and benefit for both parties carrying out the transaction. If the pillars and conditions of the mortgage are not fulfilled or violate the terms and conditions in Islam and the elements of benefit, the law is declared null and void.